Enhancing organizational performance through digital skills and capabilities: A study of industrial estates - Maungmee, Saranthon; Bhumpenpein, Nalinpat (Edelweiss Applied Science and Technology, 2025)
This research develops and evaluates a framework for enhancing organizational performance through digital skills and capabilities using a mixed-method approach, integrating qualitative and quantitative research to analyze nine key factors influencing digital transformation. The study categorizes organizations into large-scale industries (Group AA) and small-to-medium industries (Group BB) and employs literature reviews, self-assessment surveys, and in-depth interviews for data collection. The Maturity Assessment, Implementation, and Outcome Evaluation stages guide the research framework to systematically assess digital adoption, execution strategies, and performance outcomes. Findings indicate that Group AA has higher digital maturity, particularly in IT capabilities, leadership, and innovation management, whereas Group BB faces challenges in infrastructure readiness, innovation adoption, and strategic implementation. The framework’s acceptance and effectiveness are assessed through four dimensions: understanding, readiness, effectiveness, and sustainability, revealing that structured digital strategies enhance organizational performance by aligning technology adoption with business goals, workforce capabilities, and leadership vision. The study suggests further customization of digital transformation approaches for SMEs, ensuring they receive adequate support in technology investment, employee training, and strategic alignment to overcome operational constraints and achieve long-term competitiveness in the digital economy.